Heightened emotion processing as a compensatory mechanism in persons with Alzheimer's disease: Psychological insights from the tri-network model - Warren, Alison (Frontiers in Dementia, 2022)
Social and emotional communication is an integral tenant of life quality and well-being. Aberrations in functional connectivity can alter social emotional behavior in numerous disease states, including dementia. This paper aims to review the major network changes observed in Alzheimer’s disease, with a focus on the tri-network model. The central executive network, default mode network, and principally the salience network will be discussed as they relate to both pathology and compensatory behavioral manifestations in persons with dementia. The psychological and behavioral correlates of these network changes will be reviewed with the intent of increasing understanding about the conscious experience and communication modalities utilized by persons with dementia, the understanding of which may promote meaningful communication with care providers and loved ones. This paper further seeks to reframe social emotional communication methods used by persons with dementia by marrying current knowledge of neuroscience, psychology, and person-centered care. In this way, a perspective is offered that considers the heightened emotional states experienced by persons with dementia as a potential compensatory mechanism that may hold practical value under some circumstances. The many ways in which the brain adapts to physical and psychological changes, aging, and injury are still under exploration. Emotion processing may provide clinical insight into the subjective experience of dementia in this regard. Emotions, therefore, may serve to promote social bonds, provide an avenue for nonverbal communication, and act as a construct to maintain agency in persons who ultimately lose autonomy.